Infiltrated photonic crystal fiber: experiments and liquid crystal scattering model - Lorenz, Alexander; Schuhmann, Rolf; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Tuning quantum-dot based photonic devices with liquid crystals - Piegdon, Karoline A.; Declair, Stefan; Förstner, Jens; Meier, Torsten; Matthias, Heiner; Urbanski, Martin; Kitzerow, Heinz-Siegfried; Reuter, Dirk; Wieck, Andreas D.; Lorke, Axel; Meier, Cedrik (Optics Express)
Microdisks made from GaAs with embedded InAs quantum dots are immersed in the liquid crystal 4-cyano-4’-pentylbiphenyl (5CB). The quantum dots serve as emitters feeding the optical modes of the photonic cavity. By changing temperature, the liquid crystal undergoes a phase transition from the isotropic to the nematic state, which can be used as an effective tuning mechanism of the photonic modes of the cavity. In the nematic state, the uniaxial electrical anisotropy of the liquid crystal molecules can be exploited for orienting the material in an electric field, thus externally controlling the birefringence of the material. Using this effect, an electric field induced tuning of the modes is achieved. Numerical simulations using the finite-differences time-domain (FDTD) technique employing an anisotropic dielectric medium allow to understand the alignment of the liquid crystal molecules on the surface of the microdisk resonator.
Keywords: tet_topic_qd; tet_topic_microdisk

Photonic crystal fiber with a dual-frequency addressable liquid crystal: behavior in the visible wavelength range - Lorenz, A.; Kitzerow, Heinz-Siegfried; Schwuchow, A.; Kobelke, J.; Bartelt, H. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Optical time-of-flight measurement based on data transmission in a ring oscillator - Noé, Reinhold; Koch, Benjamin; Sandel, David (OPTICS EXPRESS)

Optical resonances of bowtie slot antennas and their geometry and material dependence - Guo, Hongcang; Meyrath, Todd P.; Zentgraf, Thomas; Liu, Na; Fu, Liwei; Schweizer, Heinz; Giessen, Harald (Optics Express)

Resonances in complementary metamaterials and nanoapertures - Rockstuhl, Carsten; Zentgraf, Thomas; Meyrath, Todd P.; Giessen, Harald; Lederer, Falk (Optics Express)

Phased-array cancellation of nonlinear FWM in coherent OFDM dispersive multi-span links - Nazarathy, Moshe; Khurgin, Jacob; Weidenfeld, Rakefet; Meiman, Yehuda; Cho, Pak; Noé, Reinhold; Shpantzer, Isaac; Karagodsky, Vadim (OPTICS EXPRESS)

Coherent optical communication: Towards realtime systems at 40 Gbit/s and beyond - Pfau, T.; Hoffmann, S.; Adamczyk, O.; Peveling, R.; Herath, V.; Porrmann, M.; Noé, Reinhold (OPTICS EXPRESS)

High-speed endless optical polarization stabilization using calibrated waveplates and field-programmable gate array-based digital controller - Hidayat, Ariya; Koch, Benjamin; Zhang, Hongbin; Mirvoda, Vitali; Lichtinger, Manfred; Sandel, David; Noé, Reinhold (OPTICS EXPRESS)

Ultrabroadband 50-130 THz pulses generated via phase-matched difference frequency mixing in LiIO_3 - Zentgraf, Thomas; Huber, Rupert; Nielsen, Nils C.; Chemla, Daniel S.; Kaindl, Robert A. (Optics Express)

The origin of magnetic polarizability in metamaterials at optical frequencies - an electrodynamic approach - Rockstuhl, Carsten; Zentgraf, Thomas; Pshenay-Severin, Ekaterina; Petschulat, Jörg; Chipouline, Arkadi; Kuhl, Jürgen; Pertsch, Thomas; Giessen, Harald; Lederer, Falk (Optics Express)

Resonance hybridization in double split-ring resonator metamaterials - Guo, Hongcang; Liu, Na; Fu, Liwei; Meyrath, Todd P.; Zentgraf, Thomas; Schweizer, Heinz; Giessen, Harald (Optics Express)

On the reinterpretation of resonances in split-ring-resonators at normal incidence - Rockstuhl, Carsten; Lederer, Falk; Etrich, Christoph; Zentgraf, Thomas; Kuhl, Jürgen; Giessen, Harald (Optics Express)

Electromagnetic field structure and normal mode coupling in photonic crystal nanocavities - Dineen, C.; Förstner, Jens; Zakharian, A.R.; Moloney, J.V.; Koch, S.W. (Optics Express)
The electromagnetic field of a high-quality photonic crystal nanocavity is computed using the finite difference time domain method. It is shown that a separatrix occurs in the local energy flux discriminating between predominantly near and far field components. Placing a two-level atom into the cavity leads to characteristic field modifications and normalmode splitting in the transmission spectra.
Keywords: tet_topic_phc

PMD tolerance of polarization division multiplex transmission using return-to-zero coding - Hinz, S; Sandel, D; Wust, F; Noé, Reinhold (OPTICS EXPRESS)

PMD tolerance of polarization division multiplex transmission using return-to-zero coding - Hinz, S; Sandel, D; Wust, F; Noé, Reinhold (OPTICS EXPRESS)